Logistic problem - Limones Nava, Ana Elizabeth; Rodríguez Cisneros, Adriana Lizbeth; Rocha Vázquez, Thamara Anahí (UANL. Facultad de Contaduría Publica y Administración, 2015)
The purpose of this research is to learn more about logistic problems and how it can be solved, and to discuss about the different document reviews that can be applied. This is a complete documentary investigation which was based by a company interview. The company is dedicated to the transport of goods both import and export, it spent more money and time, because 8 suppliers was sending 3 trucks for each one to transported their products to a warehouse, the solution was that only a truck transported all products. This study case provides a comprehensive review of literature and it is primarily documentary and therefore does not any other kind of data, except document reviews.